The complete mitochondrial genome of Labidocera rotunda Mori, 1929 (Copepoda: Calanoida) from Jeju Island, Korea. Issue 9 (2nd September 2022) - Jun, Jimoon; Jeong, Hyeon Gyeong; Choi, Hyeongwoo; Woo, Hyunmin; Jeon, Donggu; Seo, Young-Jin; Eyun, Seong-il
Abstract: We sequenced the complete mitochondrial genome of the copepod Labidocera rotunda (family Pontellidae) collected from Ihotaewoo Beach in Jeju, Korea. The mitochondrial genome was 16, 564 bp in length and contained 13 protein-coding genes (PCGs), 22 transfer RNAs, and two ribosomal RNAs. The concatenated phylogenetic tree of L. rotunda was reconstructed using the maximum-likelihood method based on the eight PCGs obtained from eight species of copepods including L. rotunda . The results of the phylogeny analysis showed that L. rotunda was closely related to the family Temoridae among the three families. The complete mitochondrial genome of L. rotunda analyzed for the first time in this study provides insight into the phylogenetic and evolutionary relationship of Labidocera .